2015
DOI: 10.1186/s13098-015-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy is associated with insulin resistance independent of metabolic syndrome

Abstract: BackgroundTo determine the association of insulin resistance, metabolic syndrome (MetS) with peripheral neuropathy (PN).MethodsThis cross-sectional study consisted of 2035 subjects in Shanghai who were classified as with MetS and without MetS. The new International Diabetes Federation (IDF) criterion was used to define MetS. HOMA-IR was applied to evaluate insulin resistance. All subjects underwent complete foot examination. PN was assessed according to the neuropathy symptom and neuropathy disability scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
6
31
2
2
Order By: Relevance
“…This study also demonstrated an independent association of waist circumference with DPN after adjusting for demographics and other metabolic components. Similar results have been demonstrated by two others studies performed in China and Germany (22, 36). Moreover, low physical activity is associated with DPN (22), as patients with T2DM and DPN seem to be less active compared to T2DM subjects without DPN (43).…”
Section: Individual Mets Components and Dpnsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also demonstrated an independent association of waist circumference with DPN after adjusting for demographics and other metabolic components. Similar results have been demonstrated by two others studies performed in China and Germany (22, 36). Moreover, low physical activity is associated with DPN (22), as patients with T2DM and DPN seem to be less active compared to T2DM subjects without DPN (43).…”
Section: Individual Mets Components and Dpnsupporting
confidence: 92%
“…The MetS by definition comprises obesity, insulin resistance, hypertension, hypertriglyceridemia, and dyslipidemia, and its coexistence with diabetes has been described to be associated with the development of DPN (25, 3236). The main findings of the conducted studies are presented in Table 2.…”
Section: The Mets and Dpnmentioning
confidence: 99%
“…This finding was observed although obesity was the only other MetS component significantly associated with peripheral neuropathy. Our finding is comparable to studies performed in China,25 the United States,23 and the Netherlands 31. Unlike the studies in China and Netherlands, we did not include hyperglycemia as one of the MetS components since this is already the strongest and most well‐established risk factor for peripheral neuropathy.…”
Section: Discussionsupporting
confidence: 82%
“…Participants with prediabetes also have a higher prevalence of peripheral neuropathy, but the association does not meet statistical significance in multivariable models. These results are comparable to findings in other populations including those in the United States,22, 23 another region in China,24, 25 and the Netherlands 31. Now that the evidence supporting these specific metabolic drivers of nerve injury is increasingly robust, efforts should turn to interventional studies aimed at weight loss and/or exercise in populations at high risk of peripheral neuropathy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation